2001
DOI: 10.1093/toxsci/61.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Urinary Porphyrins as a Measure of Kidney Mercury Content and Mercury Body Burden during Prolonged Methylmercury Exposure in Rats

Abstract: Changes in urinary porphyrin excretion patterns (porphyrin profiles) during prolonged mercury exposure are attributable to mercury accumulation in the kidney and to consequent effects of Hg2+ on renal porphyrin metabolism. In the present study, we evaluated the quantitative relationship of urinary porphyrin concentrations to mobilizable renal mercury content, using the metal chelator 2,3-dimercapto-1-propanesulfonic acid (DMPS) to modulate kidney mercury levels. Rats exposed to methylmercury hydroxide (MMH) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Although this is not a direct measure of mercury in the brain, studies show that the brain and kidneys are target organs for mercury following mercury exposure. For example, Pingree et al (2001) gave rats methylmercury hydroxide (MMH) (10 ppm) in drinking water for 9 weeks and determined both inorganic (Hg2?) and organic (CH3Hg?)…”
Section: Discussionmentioning
confidence: 99%
“…Although this is not a direct measure of mercury in the brain, studies show that the brain and kidneys are target organs for mercury following mercury exposure. For example, Pingree et al (2001) gave rats methylmercury hydroxide (MMH) (10 ppm) in drinking water for 9 weeks and determined both inorganic (Hg2?) and organic (CH3Hg?)…”
Section: Discussionmentioning
confidence: 99%
“…[2] Excessive production, accumulation, and excretion of porphyrins often result from metabolic aberration. Associated with abnormal heme biosynthesis, many diseases could be caused including porphyrias, [5] iron deficiency anemia, [6] liver disease, [7] and intoxication due to the overexposure to heavy metals, [8] environmental pollutants [9] , and alcohols [10] . Therefore, monitoring the composition and contents of certain porphyrins and establishing various porphyrin metabolic patterns might provide the references for the differentiation and diagnosis of porphyrin-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that urinary porphyrins can be particularly useful in measuring Hg exposure (Gonzalez-Ramirez et al 1995;Geier 2006, 2007;Geier et al 2009a, b;Kern et al 2010a,b;Woods, 1996;Pingree et al 2001). Urinary porphyrins are not a direct measure of Hg in the urine, but a measure of presence of Hg in the body (or Hg body-burden) by the level of disruption of the heme synthesis pathway that Hg causes.…”
Section: Introductionmentioning
confidence: 99%
“…The level of increase in these ''backlogged'' metabolites measured in the urine correlates with the level of disruption of this pathway and indicates the extent of Hg tissue burden. There is a high degree of statistical correlation between renal Hg burden and the urinary excretion of specific porphyrins (Pingree et al 2001). This correlation is consistently observed in animal models of Hg exposure; and the heme pathway is highly conserved across species (Gonzalez-Ramirez et al 1995).…”
Section: Introductionmentioning
confidence: 99%